Fuzzy Function Aproximation in Simulation Model - Stradal, Oktavian (Promet - Traffic&Transportation, 2007)
The paper deals with utilization of fuzzy logic for simulationmodel parameter, which is changed during simulation experiment.Additive fuzzy system is used for approximation ofcontinuous functions, whereas the relevant membership functionsare based on ellipsoidal rules. Application of that methodologyis demonstrated on the parameter adaptation relatedto simulation model of an asynchronous machine. The mentionedadaptation depends on the changing magnetic properties.